Interactive effects between pantothenic acid and ractopamine HCl (paylean®) on growth performance and carcass characteristics of growing-finishing pigs - Groesbeck, C.N.; James, B.W.; Keegan, T.P.; Lawrence, K.R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to evaluate the interactive effects between added pantothenic acid and ractopamine HCl (Paylean®) on growth performance and carcass traits of growing-finishing pigs. In Exp. 1, 156 pigs (PIC, initial BW = 56.7 ± 5.8 lb) were used in a 2 × 3 factorial with ractopamine HCl (RAC; 0 or 10 ppm) and added pantothenic acid (PA; 0, 22.5, or 45 ppm). Pigs were fed the assigned PA concentrations from 56.7 to 268.1 lb (d 0 to 98), and were fed RAC for the last 28 d before slaughter. Increasing added PA had no effect (P<0.05) on ADG, ADFI, or feed efficiency (F/G) from d 0 to d 70. A PA × gender interaction (P<0.05) was observed for ADG and F/G from d 71 to 98. Increasing PA increased ADG and F/G in gilts, but not in barrows. Added RAC for the last 28 d before slaughter increased (P<0.001) ADG and F/G for d 71 to 98 and d 0 to 98. Increasing the amount of added PA had no effect (P<0.05) on carcass traits. Adding RAC increased (P<0.001) longissimus muscle area and percentage lean. In Exp. 2, the effects of added PA on N balance of finishing pigs fed RAC were evaluated. A total of 156 barrows (PIC, initial weight = 131.6 lb) were fed added PA (0, 22.5, or 45.0 ppm) for a minimum of eight weeks. A total of 44 pigs were randomly selected from the 156 initial pigs and were moved into individual stainlesssteel metabolism creates. Pigs remained on their respective PA treatments, with or without RAC (10 ppm), for 8 d, were moved out of the collection chambers, and were fed the same diets from d 8 to 28. There were no PA × RAC interactions (P<0.05) observed. Added PA had no effect (P<0.05) on N excretion, N retention, or biological value (BV). Fecal N excretion was greater (P<0.01) for pigs fed RAC, compared with that of the pigs not fed RAC, but urinary N decreased (P<0.01) for the pigs fed RAC, resulting in no difference in total excreted N. Adding RAC increased (P<0.04) BV. No PA (P < 0.05) response was observed for ADG or F/G, and RAC increased (P<0.001) ADG and F/G from d 0 to 28.
Keywords: Growth; Pantothenic acid; Pigs; Ractopamine hcl; Vitamin; Swine